Phytonutrients in the Treatment of Gastrointestinal Cancer. - Khan, Haroon (Bentham Science Publishers, 2023)
Gastrointestinal cancer is one of the most prevalent causes of cancer-related deaths in the world. Recent research demonstrates that phytochemicals are critical in preventing and managing gastrointestinal cancer. The increased intake of phytochemicals could reduce the risk of cancer by inhibiting cancer cell proliferation, inducing apoptosis and autophagy, and suppressing angiogenesis as well as cancer cell metastasis. These mechanisms are also known to counte.